Development in C++ and python of a time structure Analysis Tool for particle beam analysis for the MINERvA Test beam experiment - Salazar Quiroz, Gerald Fernando (2016)
We present in this thesis the results of the design and programming of a temporal anal- ysis tool for experiment data MINERVA Test Beam (TbTaTool), which receives pions and electrons in the energy range corresponding to the end of the interactions of neutrinos energy states with MINERvA detector. The TbTaTool is independent, flexible and adapt- able to other contexts where we need to analyze the distribution of events over time, because it has separated datasets’ production from the tool itself. Our tool has been applied to the data (Run 2 and Run 3) that the experiment has obtained in MTest at Fer- milab, focusing on the variables of frequency of spill of the particles (MI’s spill frequency), duration of spill (MI’s spill duration) and the profile over time of packets corresponding to the delivery of the particles (time profile). Our calculations show 0.01% of difference for the frequency of spill of the particles and 9.34%, for the second variable, compared to the values indicated by the Fermilab’s Accelerators Division. Furthermore, this tool had set the basis for constructing a real time DAQ visualizator of the measurement process. Se presenta los resultados del diseño y programación de una herramienta de análisis temporal para los datos del experimento MINERvA Test Beam (TbTaTool), que recibe piones y electrones en el rango de energía correspondiente a los estados energéticos finales de las interacciones de neutrinos con el detector MINERvA. El TbTaTool es independiente, flexible y adaptable a otros contextos donde se quiera analizar la distribución de eventos respecto al tiempo. Nuestra herramienta ha sido aplicada a los datos (Run 2 y Run 3) que el experimento ha obtenido en el MTest en el Fermilab, enfocandonos en las variables de frecuencia de entrega de las partículas (MI’s spill frequency), duración de la entrega (MI’s spill duration) y el perfil en el tiempo de los paquetes correspondientes a la entrega de las partículas (Time Profile). Nuestros cálculos muestran un 0.01% de diferencia para la frecuencia de entrega de las partículas y 9.34%, para la segunda variable, frente a los valores indicados por la División de Aceleradores de Fermilab. Ademas esta herramienta ha establecido el fundamento para la construcción de visualizador del proceso de adquisición de datos en tiempo real.